2009
DOI: 10.4238/vol8-4gmr667
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype correlations in diabetic patients in Uruguay

Abstract: ABSTRACT.To differentiate among different types of diabetes is becoming an increasingly challenging task. We investigated whether the patient's genetic profile is useful to identify the particular type of diabetes, to determine the corresponding hyperglycemia pathogenesis and treat accordingly. Three hundred and thirty-eight diabetic patients, diagnosed according to American Diabetes Association criteria, were recruited from 2004 to 2008 in diabetes health reference centers. We analyzed the major gene for type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The HLA typing was performed by reverse ASO technique (Innogenetics Ltd., Belgium, UE). INS 5 ′ VNTR , rs3842753, and HLA were processed in a previous work [ 4 , 5 , 15 , 17 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HLA typing was performed by reverse ASO technique (Innogenetics Ltd., Belgium, UE). INS 5 ′ VNTR , rs3842753, and HLA were processed in a previous work [ 4 , 5 , 15 , 17 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…This complexity could be an important influence in the actual classification and treatment of this pathology. Previously, in an effort to link the current classification with advances at molecular genetics we found that in several studies a significant proportion of diabetic patients did not present a correlation between genotype and phenotype [ 4 6 ]. Type 2 diabetes (T2D) diagnosed patients using international criteria [ 7 ] presented Human Leukocyte Antigen (HLA) alleles associated with type 1 diabetes (T1D) and positive antibodies in an intermediate value between both types, thus suggesting the coexistence of both types of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases the classical diagnostic markers and risk factors analysis for various chronic complications, are not sufficient by themselves for a clinical differentiation. In a previous paper we found a high proportion of type 2 diabetes patients who presented HLA susceptibility alleles for type 1 diabetes [13] . Therefore, we propose to add the usage of a molecular marker (HLA) to the international standard criteria According to the ADA type 1 diabetes is strongly associated with specific HLA groups while in type 2 diabetes does not exist this association [14] .…”
Section: Introductionmentioning
confidence: 79%
“…For the preparation of this study were considered only those patients receiving comprehensive care of their diabetes, following a nutritional plan and presenting a good adherence to physical activity according to their functional ability within the recommendations of Asociacion Latinoamericana de Diabetes (ALAD)/ADA and medicated with one or more oral antidiabetic drugs. In turn, this population was classified based on the presence or absence of type 1 diabetes HLA susceptibility alleles described in the Uruguayan population [13] . Sample A: 93 "atypical" patients that met the following inclusion criteria: (1) Patients who had good adherence to the treatment; (2) They fulfilled the objectives of education and nutrition plans according to international guidelines; (3) Present doubts on classification of diabetic type and/or no good therapeutic response (two consecutive measurements of glicated hemoglobin within three months not reduced in 1.5% [17] ) to ADA, ALAD algorithms; and (4) Patients with susceptibility HLA alleles for autoimmune disease.…”
Section: Population Designmentioning
confidence: 99%
“…Previous research has shown that the Uruguayan population has a particular genetic behavior; in addition to its small size (three millions inhabitants), it presents such a high level of miscegenation that there are individuals that cannot currently identify their ancestors' origin. It has a tri-hybrid origin (Caucasoid, African and Amerindian) but, unlike other Latin-American countries, we do not isolate Amerindian groups Gascue et al, 2005;Mimbacas et al, 2003Mimbacas et al, , 2004Mimbacas et al, , 2007Mimbacas et al, , 2009Sans et al, 2011). Thus, this would permit us to think a priori that ethnological factors would (at least in part) cancel each other, therefore eliminating their possible blurring effect on the analysis.…”
Section: Miscegenated Populationmentioning
confidence: 90%